KUALITAS AUDIT, PROFITABILITAS, STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN, DAN UKURAN PERUSAHAAN DALAM PENGARUHNYA TERHADAP NILAI PERUSAHAAN - Dianita Meirini; Novi Khoiriawati (SUBSTANSI, 2021)
The decline in the value of the market capitalization of manufacturing companies in 2020 worth $ 309 trillion indicates that the value of manufacturing companies has declined during the COVID-19 pandemic. This study aims to determine the factors that influence the decline in the value of manufacturing companies during the covid-19 pandemic. Factors suspected and tested in this study to influence the value of manufacturing companies during the covid-19 pandemic are audit quality, profitability, capital structure, firm growth, and firm size. This research is a quantitative study using data from manufacturing companies that are regularly listed on the Indonesian Stock Exchange and submit annual reports for 2018-2020. The sample used is made up of 12 manufacturing companies with reasoned sampling as the sampling method. The results of the study indicate that profitability and capital structure have a significant positive effect on the value of manufacturing firms during the covid-19 pandemic. While firm size has a significant negative effect on the value of manufacturing firms during the covid-19 pandemic and the quality of audits and firm growth have no effect on the value of manufacturing firms during the covid-19 pandemic.